Antifungal consumption, indications and selection of antifungal drugs in paediatric tertiary hospitals in Turkey: Results from the first national point prevalence survey. (December 2018) - Çağlar, İlknur and Devrim, İlker and Özdemir, Halil and Şahbudak, Zümrüt and Sönmez, Gülsüm and Buyukcam, Ayse and Gulhan, Belgin and Kara, Ahu and Aygun, Deniz F. and Bayram, Nuri and Celebi, Solmaz and Çetin, Benhur and Nepesov, Merve İ. and Yilmaz, Ayşe T. and Kepenekli, Eda and Çiftdogan, Dilek Yilmaz and Acar, Manolya K. and Yayla, Burcu Cura and Okumuş, Canan and Ecevit, Zafer and Hatipoglu, Nevin and Kuyucu, Necdet and Kosker, Muhammed and Sen, Semra and Karbuz, Adem and Sutcu, Murat and Duramaz, Burcu Bursal and Özen, Metehan and Çiftçi, Ergin and Alabaz, Derya and Kurugol, Zafer and Kara, Ateş and Kanik, Saliha and Kilic, Omer and Oncel, Selim and Somer, Ayper and Tapisiz, Anil and Belet, Nursen and Akcan, Özge Metin and Türel, Özden and Ozkaya, Aslinur and Tezer, Hasan and Cengiz, Ali Bulent and İnce, Erdal and; ioglu, Yıldız and; bas, Emine and; oy, Emin S. and; an, Nuran
Highlights: On the study day, 314 antifungal drugs were prescribed in 301 (9.0%) of 3338 patients. Most of the antifungals were prescribed for paediatric haematology–oncology patients (35.2%), followed by neonates (19.6%). Antifungals were used for prophylaxis in 147 patients (48.8%) and for treatment in 154 patients (51.2%). Antifungal treatments were empirical in 77 patients (50.0%), diagnostic-driven in 29 (18.8%) and targeted in 48 (31.2%). Diagnostic-driven antifungal therapy was chosen mainly in PHO and HSCT units where 23 (79.3%) of 29 patients were followed. Abstract: Objectives: The aim of this point prevalence survey was to evaluate the consumption, indications and strategies of antifungal therapy in the paediatric population in Turkey. Methods: A point prevalence study was performed at 25 hospitals. In addition to general data on paediatric units of the institutes, the generic name and indication of antifungal drugs, the presence of fungal isolation and susceptibility patterns, and the presence of galactomannan test and high-resolution computed tomography (HRCT) results were reviewed. Results: A total of 3338 hospitalised patients were evaluated. The number of antifungal drugs prescribed was 314 in 301 patients (9.0%). Antifungal drugs were mostly prescribed in paediatric haematology and oncology (PHO) units (35.2%), followed by neonatal ICUs (NICUs) (19.6%), paediatric services (18.3%), paediatric ICUs (PICUs) (14.6%) and haematopoietic stem cell transplantation (HSCT) units (7.3%). Antifungals were used for prophylaxis in 147 patients (48.8%) and for treatment in 154 patients (50.0%). The antifungal treatment strategy in 154 patients was empirical in 77 (50.0%), diagnostic-driven in 29 (18.8%) and targeted in 48 (31.2%). At the point of decision-making for diagnostic-driven antifungal therapy in 29 patients, HRCT had not been performed in 1 patient (3.4%) and galactomannan test results were not available in 12 patients (41.4%). Thirteen patients (8.4%) were receiving eight different antifungal combination therapies. Conclusion: The majority of antifungal drugs for treatment and prophylaxis were prescribed in PHO and HSCT units (42.5%), followed by ICUs. Thus, antifungal stewardship programmes should mainly focus on these patients within the availability of diagnostic tests of each hospital.